The Bibionidae (Diptera) of Sardinia, with description of two new species - Haenni, Jean-Paul (Zootaxa, 2009)
The occurrence of eight species of Bibionidae is reported from Sardinia, mainly based upon recent collections made in the south-western part of the island. Two species, Dilophus bispinosus Lundström, 1913 and D. humeralis Zetterstedt, 1850, are new records for Sardinia, while two species are described as new to science: Bibio sardocyrneus sp. nov. (from Sardinia and Corsica) and Dilophus sardous sp. nov. (from Sardinia). The presence on the island of a ninth species, D. femoratus (Meigen, 1804), is considered as dubious. Finally, the following synonymy is proposed: Bibio hortulanus (Linnaeus, 1758) = Bibio siculus Loew, 1846 syn. rev.